Whole-exome sequencing of epithelial ovarian carcinomas differing in resistance to platinum therapy - Hlaváč, Viktor; Holý, Petr; Václavíková, Radka; Rob, Lukáš; Hruda, Martin; Mrhalová, Marcela; Černaj, Petr; Bouda, Jiří; Souček, Pavel (Life science alliance, 2022)
Epithelial ovarian carcinoma (EOC) is highly fatal because of the risk of resistance to therapy and recurrence. We performed whole-exome sequencing of blood and tumor tissue pairs of 50 patients with surgically resected EOC. Compared with sensitive patients, platinum-resistant patients had a significantly higher somatic mutational rate in TP53 and lower in several genes from the Hippo pathway. We confirmed the pivotal role of somatic mutations in homologous recombination repair genes in platinum sensitivity and favorable prognosis of EOC patients. Implementing the germline homologous recombination repair profile significantly improved the prediction. In addition, distinct mutational signatures, for example, SBS6, and overall mutational load, somatic mutations in PABPC1, PABPC3, and TFAM co-segregated with the resistance status, high-grade serous carcinoma subtype, or overall survival of patients. We generated germline and somatic genetic landscapes of prognostically different subgroups of EOC patients for further follow-up studies focused on utilizing the observed associations in precision oncology.
Keywords: sekvenování exomu; platina; individualizovaná medicína; epiteliální ovariální karcinom; Carcinoma, Ovarian Epithelial; Platinum; Precision Medicine; lidé; Female; Exome Sequencing; ženské pohlaví; nádory vaječníků; Humans; Ovarian Neoplasms